MAIS Notícias Sobre o Atentado à Charlie Hebdo: a Representação Social dos Religiosos Islâmicos na Folha de S. Paulo - Marchete, Ana Clara Partelli (2020)
Based on the Sociocognitive Discourse Theory (VAN DIJK, 1998; 2005; 2012; 2015; 2016), and according to the category of social representation proposed by Theo van Leeuwen (2008), this work intends to analyze discursively Folha de S. Paulo texts about the